Liquidity management and profitability. A case of listed banks in Ghana - Charles Ofori; Takyi Kwabena Nsiah; Mmieh Kwakye Raphael; Isaac Awusi Jnr; Justice Agbattey (Garuda Prestasi Nusantara Consulting, 2022)
The article is intended to uncover the connection between liquidity and profitability in such a way that each bank must preserve this link while undertaking its day-to-day operational activities. The investigation employed listed banks on the Ghana Stock Exchange from the dated 2008 - 2018. Two estimators namely the Ordinary Least Square (OLS) and the Generalized Method of Moments (GMM) were utilized. To add to existing literature, the liquidity parameters employed in this study exhibited a favorable and significant link with the dependent indicators except for quick ratio which exhibited an immaterial affiliation. In addition, a robustness assessment was employed adopting the three-stage least-squares and the findings were parallel to that of the other estimators employed. The above insights are vital as regulators concoct changing standards offering banks with an optimal degree of liquidity. Although it is widely accepted that, prior to the latest financial crisis, banks undervalued liquidity, and the trade - offs between sensitivity to liquidity fluctuations and the risk of maintaining lower-yielding liquid assets must also be weighed, as the latter will influence the capacity of banks augment earnings and expand credit.